3,3′-(p-Phenylenedimethylene)di-1H-imidazol-1-ium bis(4-nitrobenzoate)–4-nitrobenzoic acid (1/2) - Gui-Ying Dong; Xin-Hua Liu; Tong-Fei Liu; Islam Ullah Khan (Acta Crystallographica Section E, 2010)
The asymmetric unit of the title compound, C14H16N42+·2C7H4NO4−·2C7H5NO4, comprises one-half of the 3,3′-(p-phenylenedimethylene)di-1H-imidazol-1-ium dication, which lies on an inversion centre, one 4-nitrobenzoate anion and one 4-nitrobenzoic acid molecule. In the crystal, the components are linked into a two-dimensional network parallel to (110) by O—H...O, N—H...O and C—H...O hydrogen bonds.